Assessing implementation readiness and success of an e-resource to improve prelicensure physical therapy workforce capacity to manage rheumatoid arthritis - Fary, Robyn; Slater, Helen; Jordan, J.; Gardner, Peter; Chua, Jason; Payne, Carly; Briggs, Andrew (2017)
STUDY DESIGN: Prospective within-subject, cross-sectional, between-group, nested qualitative designs within an implementation science framework. BACKGROUND: Physical therapy is recommended for rheumatoid arthritis (RA) care, yet prelicensure RA curriculum time remains limited. OBJECTIVES: To determine readiness for, and success of, implementing an e-learning tool, Rheumatoid Arthritis for Physiotherapists e-Learning (RAP-eL), within the prelicensure physical therapy curriculum. METHODS: All physical therapy students in a 1-year cohort in 2014 had RAP-eL embedded in their curriculum. Rheumatoid Arthritis for Physiotherapists e-Learning is an online platform that delivers RA disease information with translation to clinical practice. Implementation readiness, determined by acceptability of RAP-eL to students, was evaluated using focus groups (n = 23). Implementation success was measured using quantitative data from a previously validated questionnaire, including changes in students' self-reported confidence in knowledge (out of 45) and skills (out of 40) in managing RA after 4 weeks of access to RAP-eL, retention of learning over 14 months, and differences in workforce readiness between students in the cohort who had access to RAP-eL and a historical control cohort. RESULTS: Acceptability of RAP-eL was confirmed from qualitative data, demonstrating implementation readiness. Short-Term improvements were observed in RA knowledge (mean difference, 16.6; 95% confidence interval [CI]: 15.7, 17.6) and RA skills (mean difference, 14.9; 95% CI: 13.9, 15.9; n = 137). Retention was demonstrated after 14 months (P < .001; n = 62). Students in the 1-year cohort who had RAP-eL embedded in the curriculum scored significantly higher on knowledge (mean difference, 3.6; 95% CI: 1.3, 5.9) and skills (mean difference, 3.3; 95% CI: 0.9, 5.7; n = 62) compared to those without RAP-eL (n = 36). Rheumatoid Arthritis for Physiotherapists e-Learning remains embedded in the curriculum. CONCLUSION: This study demonstrated both readiness and success of the sustainable imple-mentation of RAP-eL within a prelicensure physical therapy curriculum.